'How We Were Never Posthuman': Technologies of the Embodied Voice in Pamela Z's Voci. Issue 1 (February 2022) - BARRETT, G. DOUGLAS
Abstract: This article analyses composer Pamela Z's work in light of critiques of posthumanism from Black studies and sound/music studies. Z's large-scale multimedia work Voci (2003), which the artist describes as a 'polyphonic mono-opera', consists of a series of eighteen scenes that combine vocal performance with digital video and audio processing. Z manipulates these sources using the BodySynth, an alternate controller interface that converts bodily gestures into expressive control signals. Z's work has been considered through cyborgian, Afrofuturist, and posthumanist discourses. But rather than affirm her practice as fully consonant with technological visions of the posthuman, I argue that she challenges the very liberal humanism upon which the posthuman is built. For a key tenet of liberal humanism, as Alexander G. Weheliye observes, was the racial and gendered apportionment of humanity into full humans, not-quite-humans, and non-humans. We have never been completely human, he suggests, let alone posthuman. Z uses technologies of the embodied voice to confront both the posthuman imaginary and the continued effects of its ideological preconditions in racio-colonial liberal humanism. In a Voci scene entitled 'Voice Studies', for instance, Z engages the problem of 'linguistic profiling' as it applies to housing discrimination, citing the work of Stanford linguistics researcher John Baugh. Against a backdrop of percussive vocalizations, Z explains, 'Studies reveal that people can often infer the race of an individual based on the sound of their voice', subsequently playing back recordings of housing applicants containing vocal signifiers of racial difference. The article then contrasts this kind of 'aural dimension of race' found in Jennifer Lynn Stoever's notion of the 'sonic color line' with Pierre Schaeffer's attempt to separate sound from the social – as well as from bodies and identities – in his practice of acousmatic reduction. With this in mind, I show how Z construes the voice as an acous(ma)tic technology of embodiment while reframing opera's humanist legacy through Voci 's allegorical narration of the 'prehuman', 'human', and 'posthuman'. Moving with and against a posthuman imaginary, Z suggests that although we have never quite been human or posthuman, we may nevertheless narrate new versions of each.